Trusting in God Religious and Spiritual Support in Mental Health Treatment Expectations in Mexico - Stege, Alyssa M. Ramírez; Godinez, Jonathan (2022)
Religious and spiritual practices have been identified as a main source of mental health support for Latinxs to improve overall health and well-being. This qualitative secondary data analysis sought to elucidate how Mexican patients and family members engaged in religious and spiritual practices to help alleviate patients’ experiences of mental illness. Three main findings are discussed: (1) positive religious coping such as entrusting God with one’s suffering, consejos (i.e., emotional support and advice giving), and positive social supports through religious communities; (2) negative religious coping such as harmful views of God as punishing; and (3) indigenous healing practices such as engagement with curanderos (medicine doctor) and limpias (i.e., herb-based cleanses). The authors discuss these findings in the context of tensions between culturally sanctioned healing and the perception of psychotherapeutic effectiveness reported by Mexican patients and their family members. The authors also provide future directions for incorporating patients’ religious and spiritual practices into multiculturally competent treatment.
Keywords: Mental Illness; Mexico; Religious Coping; Spirituality